The international banking system : capital adequacy, core businesses and risk management - Lessambo, Felix I. (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2013)
This book provides a comprehensive and detailed understanding and analysis of banking businesses and their worldwide operations. Banks have become 'too big to fail', and too complex-to-manage in their inbound and outbound operations. This book gives the relevant details, approaches, and answers to these complex financial issues.
Includes bibliographical references and index.
oif 12/06/15
Loans
Keywords: Banks and banking, International; Banks and banking; Banking system